NOSTALGIC ELEMENTS IN INTIZAR HUSSAIN’S NOVEL "BASTI" - Dr. Muhammad Rahman; Dr. Tariq Ilyas; Dr. Mutahir Shah; Dr. Sanam Shakir; Dr. Umer Qiaz Khan Qail; Dr. Sadaf Fatima; Dr. Nazia Parveen; Syed Azwar Abbas (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2023)
Intizar Hussain is an important name in the history of Urdu fiction. He earned a lot of fame in short stories and novels. His important novels including "Basti", "Chandgahan", "Tazkira" and "Aagay Samudran Hai". The short stories include "Gali Koochay", "Kankri", "Aakhri Aadmi", "Kichway" and "Shehr-e-Afsos". There are also some Dramas . All the novels or short stories of Intizar Hussain have the effects of nostalgia in them. Due to these effects, these stories have a distinct mood. In his novel "Basti", these effects can be felt on every page. This is the reason why the researcher has kept this aspect in mind.The present article is written with reference to the nostalgic elements in Intar Hussain’s novel "Basti".